1998
DOI: 10.1029/98jb00956
|View full text |Cite
|
Sign up to set email alerts
|

Lithospheric‐scale structure across the Bolivian Andes from tomographic images of velocity and attenuation for P and S waves

Abstract: Abstract. We have developed a three-dimensional, lithospheric-scale model across the Bolivian Andes at ~20øS, based on tomographic images of velocity and attenuation for both P and S waves. Both the timing and location of volcanism are consistent with upward migration of mantle wedge asthenosphere following the removal of over thickened lithosphere.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
110
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(122 citation statements)
references
References 55 publications
12
110
0
Order By: Relevance
“…2;Whitman et al 1992;Whitman 1994;Dorbath et al 1993;Beck et al 1996;Beck and Zandt 2002;Lyon-Caen et al 1985;Watts et al 1995;Stewart and Watts 1997;Myers et al 1998;Yuan et al 2000Yuan et al , 2002Tassara 2005;Heit et al 2007;Pérez-Gussinyé et al 2008;Tassara and Echaurren 2012). These show that the high Andes form a broad region, ϳ500 km wide, where the thick crust is up to 75 km thick, but the lithosphere is less than 100 km thick.…”
Section: Lithospheric Profilesmentioning
confidence: 84%
“…2;Whitman et al 1992;Whitman 1994;Dorbath et al 1993;Beck et al 1996;Beck and Zandt 2002;Lyon-Caen et al 1985;Watts et al 1995;Stewart and Watts 1997;Myers et al 1998;Yuan et al 2000Yuan et al , 2002Tassara 2005;Heit et al 2007;Pérez-Gussinyé et al 2008;Tassara and Echaurren 2012). These show that the high Andes form a broad region, ϳ500 km wide, where the thick crust is up to 75 km thick, but the lithosphere is less than 100 km thick.…”
Section: Lithospheric Profilesmentioning
confidence: 84%
“…Other projects carried out in the region also provided important results concerning lithospheric structure, crustal-thickness variations and lateral variations in the upper mantle (e.g. Beck et al, 1996;Dorbath and Granet, 1996;Myers et al, 1998;Dorbath and Masson, 2000;Beck and Zandt, 2002). Beneath the plateau, Myers et al, (1998) found low velocities on the eastern side towards the Eastern Cordillera suggesting lithospheric delamination.…”
Section: The Central Andes At 21°s and The Altiplano Plateaumentioning
confidence: 96%
“…Beck et al, 1996;Dorbath and Granet, 1996;Myers et al, 1998;Dorbath and Masson, 2000;Beck and Zandt, 2002). Beneath the plateau, Myers et al, (1998) found low velocities on the eastern side towards the Eastern Cordillera suggesting lithospheric delamination. By combining all geophysical and geological available data McQuarrie et al (2005) suggested that both the crust and the upper mantle should have played a key role in the lithospheric evolution of the Andean plateau and supported the idea of an ongoing removal of mantle lithosphere beneath the border between the Eastern Cordillera and the Altiplano (Beck and Zandt, 2002).…”
Section: The Central Andes At 21°s and The Altiplano Plateaumentioning
confidence: 96%
See 1 more Smart Citation
“…For Beck & Zandt (2002), with given average crustal Vp and Poisson's ratio (0.25), crustal thickness in the Central Altiplano is 59-64 km, and reduces to ~50 km at 20.5°S. Lithospheric structure is also interpreted differently depending on authors, although there is a general agreement on a more asthenospheric seismic character to the south: Myers et al (1998) find that from 18°S to 20.5°S the Altiplano mantle is consistent with a mantle lithosphere down to about 125-150 km depth, and that its asthenospheric character begins at about 21°S. For Yuan et al (2002), a best fit of altitude and Bouguer anomaly with isostatic-Moho depth is obtained, assuming a felsic crust, when the lithospheric thickness is closer to 100 km than 150 km.…”
Section: Geophysical Measurements and Heterogeneity Of The Mantlementioning
confidence: 94%